Development of a High Performance Remote Terminal Unit (RTU) of Wireless SCADA System for Monitoring Performance of Micro Hydro Power Plant. Issue 1 (May 2020) - Salahuddin,; Bakhtiar,; Yusman,; Fadhli,
Abstract: Remote Terminal Unit (RTU) is one part of SCADA system that functions to collect data from the plant, RTU itself is a unit of minicomputer that is equipped with a standalone system with a smaller physical size. The main objective of this research is to develop a high performance RTU for the wireless SCADA system that is applied to monitoring the performance of microhydro power plants (MHPP). Remote terminal units are built using Arduino Uno as a control center that will regulate analog data traffic from sensors connected to the system. The Remote Terminal Unit processes data from sensors that are converted into digital data and then sent via communication devices to the Main Terminal Unit (MTU) section that is located in the remote control center. The data received from sensor consist of voltage, current, frequency and turbine rotation of a MHPP. The Remote Terminal Unit (RTU) has been able to properly acquire data received by the sensor and then send it to the Main Terminal Unit via an AX.25 protocol based communication device.